Analisis Perbandingan Optimasi Pit 24 dengan Metode Lerch Grossman 2D terhadap Estimasi dari Software Minescape di PT Indominco Mandiri (IMM), Kabupaten Kutai Timur, Provinsi Kalimantan Timur - Jhony Maxi Harjadi; Shalaho Dina Devy; Albertus Juvensius Pontus; Windhu Nugroho; Ardhan Ismail (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
An open pit exploitation activity will become less effective and cause production to not run well, resulting in the failure to meet production targets at PT. Indominco Mandiri. Therefore, to achieve production targets and obtain more optimal results, we need to plan the Design Pit Limit. The purpose of this research is to optimize the pit, find the BESR value, and compare the differences between two methods. The Lerch Grossman 2D algorithm method is believed to be able to determine the optimal pit boundary quite quickly, while the Minescape with its triangle method can calculate some unreadable sides quite accurately. The Lerch Grossman method with its economic blocks indicates that an elevation of 72 mdpl is the outer boundary of the pit that has the potential to generate a profit of 20,194,836.59, with the best consideration being a Stripping Ratio of 1:21.08. With that lower limit, an optimal pit design was created using minescape software, resulting in a coal reserve value of 1,581,870.42 tons with a profit of 14,590,646.75, which is larger and with a smaller SR of 1:19.06.